2005
DOI: 10.1152/ajprenal.00361.2003
|View full text |Cite
|
Sign up to set email alerts
|

Insulin treatment enhances AT1receptor function in OK cells

Abstract: Increased renal sodium retention is considered a major risk factor contributing to hypertension associated with chronic hyperinsulinemia and obesity. However, the molecular mechanism involved is not understood. The present study investigates the effect of insulin treatment on AT1 receptor expression and ANG II-induced stimulation of Na/H exchanger (NHE) and Na-K-ATPase (NKA) in opossum kidney (OK) cells, a proximal tubule cell line. The presence of the AT1 receptors in OK cells was confirmed by the specific bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
1
28
0
1
Order By: Relevance
“…Thus, Nickenig and colleagues [86] observed that an acute treatment with insulin promotes a significant increase of AT 1 protein expression in vascular smooth muscle cells. Similarly, Banday and coworkers [87] observed an increase of AT 1 expression and Ang II action upon Na-K-ATPase and Na/H exchanger proteins in renal cells. Finally, Golovchanko and colleagues [88] have shown that hyperinsulinemia enhances Ang II-induced NF-kappaB transcriptional activity in vascular smooth muscle cells.…”
Section: The Reverse Cross-talk -Does Insulin Modulate Ang II Action?mentioning
confidence: 71%
“…Thus, Nickenig and colleagues [86] observed that an acute treatment with insulin promotes a significant increase of AT 1 protein expression in vascular smooth muscle cells. Similarly, Banday and coworkers [87] observed an increase of AT 1 expression and Ang II action upon Na-K-ATPase and Na/H exchanger proteins in renal cells. Finally, Golovchanko and colleagues [88] have shown that hyperinsulinemia enhances Ang II-induced NF-kappaB transcriptional activity in vascular smooth muscle cells.…”
Section: The Reverse Cross-talk -Does Insulin Modulate Ang II Action?mentioning
confidence: 71%
“…The antibody used for AT 1 receptors recognized a single band of ϳ45 kDa (Fig. 5A), which has earlier been characterized for its specificity (3). Similarly, the antibody used for eNOS detected a single band of ϳ133 kDa (Fig.…”
Section: Ang Ii-induced Contraction In Aortic Rings Ang II (10mentioning
confidence: 76%
“…Insulin (10 -7 mol/L, the concentration used in most in vitro studies) [20,21] exerted significant inotropic action in normal myocytes (21.8%±0.5% of Con+Ins group vs 17.9%± 0.8% of Con group; P<0.05, n=20 myocytes from 8 hearts) ( Table 1). Although the contractile function of simulated I/R myocytes (underdoing ischemia for 15 min and reperfusion with Tyrode's solution for 30 min) could not completely recover to the level of the control group, in which the cells were perfused with Tyrode's solution for 45 min, there was no significant difference in contraction of the cells in the two groups (17.9%±0.8% of Con group vs 14.5%±0.7% of I/R group; P>0.05, n=20 myocytes from 8 hearts).…”
Section: Resultsmentioning
confidence: 99%